Pharmacokinetic Characteristics and Withdrawal Times of Amoxycillin in Ducks - Poapolathep, Amnart; Limpoka, Malinee; Noonpugdee, Chartchai; Phaochoosak, Napasorn; Klangkaew, Naruamol; Tansakul, Natthasit; Singhasem, Saranya; Passadurak, Wanida (Agriculture and Natural Resources, 2001)
The pharmacokinetic characteristics of amoxycillin (AMX) were observed on healthy ducks. Each animal was administered intravenously (i.v.), intramuscularly (i.m.), subcutaneously (s.c.) and orally (p.o.) at a single dose level of 20 mg/kg body weight. The amoxycillin in plasma was detected up to 5 hours (h) after i.v. and i.m. administration but it was found up to 10 h and 6 h after s.c. and p.o. administration, respectively. However, the drug could be absorbed at the peak plasma level within 30 min after i.m and s.c. administration while it was detected at 60 min after p.o. administration. The pharmacokinetic parameters after i.v. administration were as follows; the elimination half-life (t1/2β) = 42.0 ± 3.5 min, the elimination rate constant (Kel) = 2.87 ± 0.31 h-1, the apparent volume of distribution (Vd(area)) = 0.75 ± 0.21 l/Kg, the total body clearance (ClB) = 1.59 ±0.52 l/Kg/h and bioavailability following i.m., s.c. and p.o. administration were 93.33 ± 5.23 %, 91.11 ± 7.41 % and 34.67 ± 5.06 %, respectively. Finally these available data could be used for establishing the dosage regimen as well as to allow the preslaughter withdrawal times and maximum residue limits for ducks.